Determining cost-opportunity incurred by Hospital Nacional Cayetano Heredia in normal vaginal deliveries attention 2007 - Acho Mego, Segundo (2015)
Objective: To identify cost-opportunity that Hospital Nacional Cayetano Heredia (HNCH) presents for spontaneous normal vaginal deliveries. Design: Descriptive, transversal, observational study. Setting:Department of Gynecology and Obstetrics, Hospital Nacional Cayetano Heredia, Lima, Peru. Material: Clinical charts of patients attended for non complicated vaginal deliveries. Interventions: Clinical charts of 2 700 normal vaginal deliveries attended from January through December 2007 were reviewed and distributed according to mode of financing either by Sistema Integral de Salud (SIS) or by pocket payment; also SIS rejected cases were considered. Statistical analysis was done with commercial software. Main outcome measures: Shadow cost, costopportunity by SIS, pocket expense, cases rejected by SIS. Results: The total cost for spontaneous normal vaginal deliveries attended at HNCH was S/. 1.1016.880.5 nuevos soles, cost-pportunity by SIS was S/. 243.197.9 nuevos soles and for full payment mode S/. 32.131.0 nuevos soles. Losses for SIS rejections were S/.107.434.6 soles. The lack of SIS refund to HNCH constituted 10.54% of all spontaneous normal vaginal deliveries admitted by SIS during the year 2007. Conclusions: Seventy eight per cent of spontaneous vaginal deliveries are non complicated deliveries, which means that HNCH is performing other resolutivity resolution level; based in the shadow price, a loss of S/. 741.551.6 nuevos soles was generated in 2007.